Perancangan Access Open Journal System (AOJS) dengan menggunakan Framework Codeigniter dan ReactJs - Muhammad Wali; Lukman Ahmad (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2018)
Open Journal Systems (OJS) is a web-based content management system specifically designed to handle the entire process of scientific publication management. The Ministry of Research, Technology and Higher Education also develops its own index, namely SINTA (Science and Technology Index) which is expected to not only refer to the journal index Scopus. The relationship between Access Indexing and OJS is inseparable where the OJS is a facility in managing journal publications and Access Indexing is a feature to disseminate journal articles to journal searches. This study tries to build an Access Open Journal Systems (AOJS) model that can be used as a form of publication and publishing management on international indexing. The application allows updating of data/content and sharing from various online journal sources. Access Open Journal Systems (AOJS) can enable end-user users, and still refer to international publishing management standards. It is expected that Access Open Journal Systems (AOJS) can increase publication and management of publishing electronically and be fully implemented by authors, publishers, and partners of reviewers. The Access Open Journal Systems (AOJS) application will take the Open Knowledge Systems (OJS) Public Knowledge Project (PKP) model, with the reason that the Open Journal Systems (OJS) is one of the most widely used OJS and is a recommendation from the Ministry of Research and Technology with PDII LIPI in obtaining National Journal Accreditation (ARJUNA) and facilitates researchers to see, adapt, and modify for the purposes of this study. Broadly speaking this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. Specifically, the output to be achieved Prototype as technology engineering: This research will produce a prototype Open source Access Open Journal Systems (AOJS) software, which can be used by journal publishing managers and to support content publication. The results of this study are an open source software called Open source Access Open Journal Systems (AOJS) and developed with framework CodeIgniter and React-Js.